(untitled) (Global Journal of Human-Social Science, 2021)
The entire world is linked up as a global village by information technology which connects people worldwide. Usage of information technology in social media increases its popularity among youths, especially universities, politicians, and public and private workers. The most significant innovations of men that have brought people together from every race, religion, and nationality are the Internet with social media sites such as Twitter, Facebook and Gab that are continually connecting billions of people in the world who share their ideas and opinions instantly. These so-called ideas and thoughts shared on the Internet to some extent, bear several ill consequences and online harassment, trolling, cyber-bullying, and hate speech. Hate speech as any tweet promotes violence against other people based on racial segregation, ethnicity bais, nationality, sexual orientation, gender identity, religious affiliation, age, disability, or diseases. Although several governments and social media sites are trying to curb the hate speech, it is still plaguing our society. The Twitter, Facebook, Gab etcetera are social media that promotes free speech. It allows users to post contents that may be hateful without any fear of repercussion, leading to suspension orders for violating its terms of service, namely, abusive or hateful behaviour.